2009
DOI: 10.1134/s0036023609020144
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-chemical calculation of the thermodynamics of multistep hydrolysis of MX4 molecules (M = C, Si, Ge; X = H, F, Cl) in the gas phase

Abstract: -The standard enthalpies, entropies, and Gibbs free energies of separate stages of the multistep hydrolysis of MX 4 molecules (M = C, Si, Ge; X = H, F, Cl) in the gas phase at 298 K were calculated by the G3 high-precision quantum-chemical method of calculation of thermodynamic parameters. The trends in these parameters were analyzed for each group of molecules. The calculated thermodynamic parameters make it possible to estimate the theoretical limits for the contents of water and hydrolysis products in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…(3) and (4)). The above chemical scheme is also typical of the hydrolysis and ammonolysis of chlorides and fluorides of the carbon family elements [14,[20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…(3) and (4)). The above chemical scheme is also typical of the hydrolysis and ammonolysis of chlorides and fluorides of the carbon family elements [14,[20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…14 Other studies have found silane hydrolysis to be kinetically slow at RT, with silanols as the reaction product rather than SiO 2 . 15,16 Mitsui et al determined the amount of trace water in pure monosilane to be about 20 ppb at RT. 17 While this may appear to be a low value, it corresponds to a water partial pressure of 2 × 10 −5 mbar at an absolute pressure of 1000 mbar.…”
Section: Introductionmentioning
confidence: 99%